(untitled) (World Bulletin of Social Sciences, 2022)
This research came in the introduction and the concept of affliction, and the meaning of affliction and sedition, and then explained the Sunnah of ALLAH Almighty in scrutiny and that it is a general Sunnah for all people. I dealt with the manifestations of affliction by showing the affliction in money, the affliction in the body, the affliction of the boy, and the affliction of the wife, with examples of that. I mentioned two examples of that, the Battle of Uhud and the Battle of the Trench, then I mentioned pictures and examples of the trial of the believers by deceiving the hypocrites. The study concluded with a statement of the importance and the need to adhere to patience and belief, whatever the circumstances and circumstances, with specific points